2010
DOI: 10.1016/j.jelectrocard.2010.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Unnecessary arrhythmia monitoring and underutilization of ischemia and QT interval monitoring in current clinical practice: baseline results of the Practical Use of the Latest Standards for Electrocardiography trial

Abstract: Purpose-To examine the appropriate use of arrhythmia, ischemia, and QTc interval monitoring in the acute care setting.Methods-We analyzed baseline data of the PULSE Trial, a multi-site randomized clinical trial evaluating the effect of implementing ECG monitoring practice standards. Research nurses reviewed medical records for indications for monitoring and observed if arrhythmia, ischemia, and QT interval monitoring were being done on 1,816 patients in 17 hospitals.Results-Almost all (99%) patients with an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 16 publications
1
39
0
1
Order By: Relevance
“…In most of the studies 2,5,7,9,11 in this review, researchers reported that patients who had telemetry ordered did not meet class I and class II indications. Furthermore, arrhythmic events were infrequent and clinically insignificant.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…In most of the studies 2,5,7,9,11 in this review, researchers reported that patients who had telemetry ordered did not meet class I and class II indications. Furthermore, arrhythmic events were infrequent and clinically insignificant.…”
Section: Resultsmentioning
confidence: 93%
“…These results suggest that the practice standards do not address several noncardiac conditions that physicians often monitor on telemetry units 5,6,8 and thus may not apply to patients with primary medical diagnoses. 5 For example, in a randomized controlled trial by Funk et al, 9 28.2% of patients admitted to cardiac units from 17 hospitals had a noncardiac primary diagnosis; these patients may not be appropriate for monitoring for arrhythmia, ischemia, and increased QT interval. Of the 7 diagnoses common to both hospital admission via the emergency department and telemetry unit admission, pulmonary disease and respiratory distress (ie, chronic obstructive pulmonary disease or pneumonia) 11,13 are 2 conditions without indications for ECG monitoring per AHA practice standards.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Among patients with an indication for ischemia monitoring, only 34.5% had the ST-segment monitoring feature activated on the monitor, but 26.3% of patients with no indication for ischemia monitoring also had this feature activated.…”
Section: Appropriate Use Of Technologymentioning
confidence: 95%
“…18 Baseline data on quality of care showed substandard practice related to ECG monitoring, including incorrect electrode placement, inaccurate rhythm interpretation, overmonitoring for arrhythmias, underuse of ischemia monitoring, and failure to monitor for QTc prolongation when indicated. 6,19 In the current phase of the PULSE trial, we are testing whether the online ECG monitoring education program and the strategies to implement and sustain changes in practice will enhance nurses' knowledge and the quality of ECG monitoring, ultimately leading to improved outcomes for patients.…”
Section: Improving Continuous Ecg Monitoring Practicesmentioning
confidence: 99%